FORMULASI DAN EVALUASI FISIK SEDIAAN BLUSH ON POWDER DENGAN EKSTRAK BUNGA TELANG (clitoria ternatea) SEBAGAI PEWARNA ALAMI - Putri, Faradhilah Lutfiyana; Marliana, Elsa (Jurnal Inkofar, 2025)
Cosmetics are broadly categorized into skincare and decorative products, the latter providing short-term aesthetic effects on the skin. One such product is blush-on powder, which is characterized by its fine texture, ease of application, and adjustable color intensity. In decorative cosmetics, dyes play a crucial role. Anthocyanins, natural pigments found abundantly in plants such as butterfly pea flower (Clitoria ternatea), offer potential as a natural dye due to their vivid red to deep purple color and high anthocyanin content (172.833 mg/100g). These pigments exhibit greater stability in acidic conditions, which can be enhanced by adding organic acids. This study aims to formulate a blush-on powder using butterfly pea flower extract as a natural dye and to evaluate the effect of varying concentrations of zinc stearate (3%, 5%, and 7%) on the product’s physical properties. The extract was obtained via maceration using a 96% ethanol and 10% citric acid solution (1:9 ratio). The resulting blush-on formulations underwent physical evaluations—including organoleptic tests, pH, texture, homogeneity, adhesion, and flowability—on days 0, 1, 7, and 14. All formulas met the requirements for pH, homogeneity, appearance, and adhesion stability over 14 days. However, the flowability results did not meet standard criteria. Among the three formulas, the one with 7% zinc stearate showed the highest adhesion. In conclusion, butterfly pea flower extract is suitable as a natural dye in blush-on powder formulations, and increasing zinc stearate concentration enhances product adhesion to the skin